Factors Affecting Students' Engagement in Learning English for Specific Purposes - Mardia, Sitti Indah; Nurfaidah, Sitti; Amin, Syarif; Faridawati, Faridawati; Syarif, Andi Rachmawati (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2024)
This qualitative research investigates the various factors that influence student engagement in English for Specific Purposes (ESP) learning environments. By conducting semi-structured interviews with seven non-English major students at a private university in Southeast Sulawesi, the study offers in-depth insights into the experiences and perceptions of these students. The collected data were meticulously analyzed using thematic analysis, with Kahu's (2013) theoretical framework serving as a reference point for interpreting the findings. The research revealed that a significant number of students who attended English for Economics classes felt highly engaged in their learning process. Key factors contributing to this engagement included a strong interest in the course content and a high level of self-confidence among students. Additionally, the implementation of interactive teaching methods, the integration of technology in the classroom, and the relevance of the course content were found to be critical in enhancing student engagement. The roles of both students and teachers, characterized by effective interactions and collaborative efforts, also emerged as vital components. Furthermore, the study highlighted the importance of a well-structured classroom setting in fostering a conducive learning environment. These findings underscore the multifaceted nature of student engagement, emphasizing the need for a comprehensive approach that addresses both internal and external factors.